The Effect of Motor Performance on Sportive Performance of Children in Different Sports Branches - AKTUG, Zait Burak; IRI, Ruckan (Asian Journal of Education and Training, 2018)
The aim of the study is to investigate the relationship between motor performances of children aged 10-14 years and ball striking speeds made by specific technique and to determine motor performance differences between the branches. A total of 64 children (football = 22, volleyball = 19, tennis = 23) aged 10-14 years participated in the study. The motor performances of the children participating in the study were determined with the Dordel Koch Test and the ball hitting velocities with the radar instrument. The Spearman correlation analysis was used to determine the relationship between ball hitting velocities and motor performance, and the Kruskal-Wallis test was used to determine the difference between the engine performances of the branches. According to the results obtained, there was a positive correlation between the DKTstanding long jump performance of the soccer players and the shooting speeds, between the volleyball players’ DKTshuttle and DKTpush-up performances and the service speeds, between the DKTshuttle and DKTpush-up performances of the tennis players and service and forehand strokes p<0.01. It was determined that soccer players had higher performance than both tennis players and volleyball players in the DKTpush-up test, while football players in DKTbalance test had lower performance than both tennis players and volleyball players p <0.05. As a result, it has been found that motor performances differ according to the children’s branches. In addition, it is considered that the requirements of the sports branch (active use of the lower extremity, volleyball and upper extremity in the football) are effective on motor performance.